The Study of Maternal Factors and Their Association with Risk of Preterm Birth - Alaa Al-Naama (17075063) (2023)
Objective The objective is to study maternal factors and their association with preterm birth (PTB). We hypothesize that certain maternal factors increase the risk of PTBs. Design A retrospective study recruiting women in labor at WWRC from June 2022 until February 2023. Method A cohort of 163 cases of which 59 (36.2%) were PTB (gestational age: <37 weeks) and 101 (62%) term births (gestational age: ≥ 37 weeks) were recruited. Clinical and demographic data of patients such as age, BMI, glycemic status, blood pressure (BP) status, and Group B streptococcal (GBS) infection status were collected via Cerner, the hospital’s electronic medical records. Results For maternal age, 9 PTBs (15.3%) and 5 TBs (5%) were born to mothers aged ≤25years, 39 PTBs (66.1%) and 71 TBs (70.3%) were born to mothers aged >25- ≤35 years, and 11 (18.6%) PTBs and 25 TBs (24.8%) were born to mothers aged >35 years. In terms of BMI, 2 PTBs (3.4%) and 4 TBs (3.9%) were born to underweight mothers (BMI: <18.5), 18 PTBs (30.5%) and 39 TBs (38.6%) were born to normal weight mothers (BMI: 18.5-24.9), and 39 PTBs (66.1%) and 58 TBs (57.4%) were born to overweight mothers (BMI: >25). For glycemic status, 40 PTBs (67.8%) and 71 TBs (70.3%) were born to non-diabetic mothers, 8 PTBs (13.6%) and 24 TBs (23.7%) were born to mothers with gestational diabetes mellitus (GDM), 8 PTBs (13.6%) and 2 TBs (2%) were born to mothers with type 1/type 2 diabetes mellitus (DMI/DMII), and 3 PTBs (5.1%) and 4 TBs (4%) were of unknown diabetes status. As for blood pressure (BP) status, 55 PTBs (93.2%) and 98 TBs (97%) were born to mothers with normal BP range (<120/80), and 4 PTBs (6.8%) and 3 TBs (3%) were born to mothers with abnormal BP status (preeclampsia, gestational hypertension, or chronic hypertension). For GBS status, 18 PTBs (30.5%) and 20 TBs (19.6%) were born to GBS-positive mothers, 33 PTBs (55.9%) and 78 TBs (77.2%) were born to GBS-negative mothers, and 8 PTBs (13.6%) and 3 TBs (3%) were of unknown GBS status. Conclusion Our current data suggests that maternal age, BMI, and GBS status are the most likely maternal factors associated with PTB. However, a larger sample size is necessary to support such findings. Future studies aim to recruit further cases including additional maternal factors such as preterm history, ethnicity, and presence of chorioamnionitis.